A Survey for Examining the Effects of COVID-19 and Infection Control Measures in Older Persons With Mild Cognitive Impairment and Dementia and Their Caregivers - Porcari, Desirée E.; Palmer, Katie; Spalletta, Gianfranco; Ciullo, Valentina; Banaj, Nerisa (Frontiers in Psychiatry, 2020)
Background: During the first wave of the COVID-19 pandemic, many non-urgent outpatient services in Italy were closed due to the Government-enforced lockdown period. So far, little is known about what effect the pandemic, quarantine measures, and reductions in medical services had on people with cognitive impairment and their caregivers. Objective: To describe a telephone and postal questionnaire to assess the impact of the COVID-19 pandemic during the first Italian lockdown period (11 March - 4 May 2020) on outpatients referred to an Italian memory clinic and their caregivers. Design: Psychiatrists, neuropsychologists, and epidemiologists developed two surveys: one for patients with Mild Cognitive Impairment and other cognitive disorders, the other for their relatives and/or caregivers. The surveys include five sections: a) socio-demographic information and access to technology devices; b) individual COVID-19 protection methods; c) knowledge about COVID-19; d) the effect of COVID-19 on daily life and e) the effect of COVID-19 on emotional state. Conclusion: Until an effective vaccine is developed it is likely that future waves of COVID-19 will result in shielding of vulnerable older adults. We believe that this instrument will be useful as a tool to collect information and help clinician to promptly respond to changes in patient’s cognitive, psychiatric, and somatic health needs, and to help for future planning in subsequent quarantine periods.